Parents' perspectives on indulgence: remembered experiences and meanings when they were adolescents and as current parents of adolescents. Issue 3 (2nd September 2017) - Rehm, Marsha; Darling, Carol A.; Coccia, Catherine; Cui, Ming
ABSTRACT: This study used interviews to question 29 parents of adolescents regarding their perceptions of parental indulgence they had experienced and practice now as parents. The study was based on socialization and symbolic interactionism theories with qualitative analysis techniques being used to identify thematic findings. Four parents had not been indulged and did not believe they indulged their children. Four parents perceived they had been indulged themselves and have continued the same pattern with their adolescents. The majority of parents (21) had not been indulged. However, they now indulged their adolescents in a number of ways: lack of rules and daily health routines, few expectations to contribute to household chores, giving in to demands, and solving problems for adolescents rather than allowing them to take responsibility. Supported by symbolic interactionism, results indicate that many parents interpret indulgence as a form of love and a way to support their adolescents'.